Treatment Outcomes of Mandibular Fractures in Dogs: A Retrospective Study of 24 Cases - Raj H, Pushkin; Vishnu Vardhan Reddy, Puli; Simon, Shiju; Ali, Mohamed; Prasad, Arun; Shafiuzama, Mohamed (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Mandibular fractures present unique surgical challenges due to their anatomical complexity. This retrospective study of 24 dogs examines  fracture patterns, management strategies, and outcomes. Road traffic accidents were the predominant etiology (n=13), followed by  dog bites (n=7), falls (n=3), and horse kicks (n=1). Patients were presented with signs of oral bleeding, jaw mal-alignment, swelling, and  reluctance to eat. A high incidence occurred in dogs under one year (n=12) and Indian Pariah breed (n=20), with males predominating  (n=16). Bilateral fractures occurred in 13 cases, while 8 had multiple fractures. Fracture distribution was: canine-premolar region (n=10),  symphyseal separation (n=6), third-fourth molar region (n=4), last molar-ramus (n=4), incisor-canine (n=3), first-second molar (n=3),  with one concurrent maxillofacial fracture. Stabilization techniques employed were circumferential wiring, K-wires, plates (cuttable,  SOP), and external fixation. Postoperative care included soft diet, antibiotics, analgesia, and antiseptic rinses.
Keywords: Dog; Fracture; Mandible; Road traffic accident